Kajian Komposisi Sebagai Dasar Pemahaman Bentuk pada Komputasi Perancangan Arsitektur - Tomasowa, Riva (ComTech: Computer, Mathematics and Engineering Applications, 2012)
Composition and CAAD are closely related to structure logic. Composition is built by numbers which are also the language of CAAD frame algorithm. This bond provides the opportunity and privilege to help map the composition of CAAD into concrete manifestation. This paper examines both the composition of the basicconcepts introduced to students and the application to the computerized design. Awareness of students as designers is reviewed towards the tools and their potential availability in the case of form composition from the basic field. The specialty of this tool is able to redefine the creativity path to be logical and measurable. This opportunity provides acceleration towards form searching and balanced expression according to the designer?s interpretation. The user?s ability to optimize the modeling tool helps start the formation of the basic ideas. Starting from digital sketch, it gives room for the evolution and development of a vast alternative design.